2016
DOI: 10.1038/srep35302
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-145 inhibits VSMC proliferation by targeting CD40

Abstract: Recent studies have demonstrated functions of miR-145 in vascular smooth muscle cells (VSMCs) phenotypes and vascular diseases. In this study, we aim to determine whether CD40 is involved in miR-145 mediated switch of VSMC phenotypes. In cultured VSMCs, the effects of miR-145 and CD40 on TNF-α, TGF-β, and Homocysteine (Hcy) induced cell proliferation were evaluated by over-expression of miR-145 or by siRNA-mediated knockdown of CD40. We also used ultrasound imaging to explore the effect of miR-145 on carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…miR-935 suppresses tumorigenesis of gastric signet ring cell carcinoma by targeting Notch1 [ 78 ]. miRNA-145 inhibits VSMC proliferation by targeting CD40 [ 79 ]. VSMC differentiation signals potentially can be fine-tuned or amplified by miR-143/145 through Notch and SRF in parallel pathways [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-935 suppresses tumorigenesis of gastric signet ring cell carcinoma by targeting Notch1 [ 78 ]. miRNA-145 inhibits VSMC proliferation by targeting CD40 [ 79 ]. VSMC differentiation signals potentially can be fine-tuned or amplified by miR-143/145 through Notch and SRF in parallel pathways [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated that PDGF-bb treatment differentially regulated the expression of miRNAs in VSMCs. In some studies, PDGF-bb treatment induced the up-regulation of miRNAs such as miR-15b, miR-541 and miR-146b-5p [ 22 – 24 ]; while in other experiments, PDGF-bb treatment suppressed the expression of miRNAs such as miR-599, miR-21 and miR-145 [ 14 , 25 , 26 ]. In the present study, we showed that PDGF-bb treatment suppressed the expression of miR-137.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-503 was found to inhibit PDGF-bb-induced human aortic VSMCs proliferation and migration via targeting the insulin receptor [ 13 ]. MiR-145 was found to have inhibitory effects on the VSMCs proliferation, and this inhibitory effect was mediated via targeting the CD40 [ 14 ]. On the other hand, miR-34a was found to promote proliferation of human pulmonary artery smooth muscle cells by targeting platelet-derived growth factor alpha [ 15 ], and miR-181b activated the PI3K and MAPK signaling pathways, which subsequently promoted VSMCs proliferation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-133 indirectly decreases the activity of KLF4 via downregulating the transcription factor Sp-1 (Torella et al, 2011 ). Suppression of CD40, a type I transmembrane glycoprotein receptor, is another mechanism through which miR-145 contributes to the contractile phenotype of VSMC and inhibits TNF-α -mediated VSMC proliferation (Guo et al, 2016 ). Finally, miR-143/145 deficiency negatively regulate vascular tone through impaired vasodilation which is considered to result from increased VSMC switch to the dedifferentiated phenotype (Noratal et al, 2012 ).…”
Section: Klf4 and Myocardinmentioning
confidence: 99%